Basic Ideas and Principles for Quantifying Regional Blood Flow with Nuclear Medical Techniques - Herzog, H. (Nuklearmedizin - NuclearMedicine, 1996)
The measurement of blood flow in various organs and its visual presentation in parametric images is a major application in nuclear medicine. The purpose of this paper is to summarize the most important nuclear medicine procedures used to quantify regional blood flow. Starting with the first concepts introduced by Fick and later by Kety-Schmidt the basic principles of measuring global and regional cerebral blood are discussed and their relationships are explained. Different applications and modifications realized first in PET- and later in SPECT-studies of the brain and other organs are described. The permeability and the extraction of the different radiopharmaceuticals are considered. Finally some important instrumental implications are compared.
Keywords: Blood flow; quantitation; tracer modelling; positron emission tomography; single-photon emission-computed tomography